The Effects of COVID-19 on Garuda Indonesia Airlines - Sarjono, Haryadi; Alvian, Cordirianto; Marcelino, Kelvin (Golden Ratio of Data in Summary, 2025)
Impact of the COVID-19 pandemic on Garuda Indonesia, Indonesia's national airline. Reviews Garuda Indonesia's status before the pandemic, emphasizing its critical role in the global aviation sector and its challenges, including fluctuating jet fuel prices and environmental concerns. The onset of the COVID-19 pandemic brought unprecedented disruption, leading to a sharp decline in passenger demand, stringent travel restrictions, and a global economic downturn, all of which significantly impacted the aviation industry. This study analyzes the financial consequences for Garuda Indonesia, which are characterized by declining revenues and operational challenges, as well as the implementation of strategic measures to mitigate these impacts. The study uses a comprehensive methodology, analyzing financial statements and market data to assess the airline's resilience, financial health, and adaptation strategies during the pandemic. The study highlights the airline's shift towards financial restructuring, increasing operational efficiency, and focusing on passenger-centric services as key strategies for survival. The role of government support and policies in assisting the aviation sector during this crisis is also discussed, emphasizing the need for such interventions for the industry's recovery. The paper underlines the importance of continued innovation and adaptability in the aviation industry, particularly for airlines like Garuda Indonesia, to navigate post-pandemic challenges and sustain long-term growth and development.